2008
DOI: 10.1016/j.jcrs.2008.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high-speed digital video images of vibrations of an ultrasonic tip and phacoemulsification

Abstract: The study visually showed that continuous-mode US produces chattering motion, while micropulse-mode US produces hyper-followability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…3 The tendency of nuclear fragments to bounce against the tip is known as chatter, which has been associated with damage to the corneal endothelium as a result of direct mechanical abrasion by fragments. 4 In addition, chatter results in decreased cutting efficiency and consequently longer phacoemulsification times and higher power settings, which have been reported to cause increased endothelial damage. [5][6][7] Longitudinal tip movement is also associated with reduced followability, defined as the ease by which lens fragment material can be smoothly and progressively aspirated into the tip aperture without being repulsed away.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The tendency of nuclear fragments to bounce against the tip is known as chatter, which has been associated with damage to the corneal endothelium as a result of direct mechanical abrasion by fragments. 4 In addition, chatter results in decreased cutting efficiency and consequently longer phacoemulsification times and higher power settings, which have been reported to cause increased endothelial damage. [5][6][7] Longitudinal tip movement is also associated with reduced followability, defined as the ease by which lens fragment material can be smoothly and progressively aspirated into the tip aperture without being repulsed away.…”
Section: Resultsmentioning
confidence: 99%
“…2,20 Although cavitation has been implicated as a cause of endothelial damage through the formation of free radicals, this mechanism remains controversial. [2][3][4]20,21 Surgical outcomes were graded based on visual acuity, corneal thickness, and central corneal edema 1 day postoperatively. Evidence has shown that postoperative day 1 corneal thickness and edema is an effective measure of surgically induced endothelial damage as a result of alterations in pump and barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Miyoshi et al 10 described this as lens milk. These jets of plume were clearly visible in the slow-motion film compared with the normal-speed video.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] However, all these studies were performed in a laboratory setting by simulating phacoemulsification. To our knowledge, this is the first report of the application of high-speed imaging in a real-time operating scenario during phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation